Mechanisms of chemotherapy‐induced muscle wasting in mice with cancer cachexia. Issue 1 (26th August 2021) - Murphy, Kate T.; Swiderski, Kristy; Ryall, James G.; Davey, Jonathan R.; Qian, Hongwei; Lamon, Séverine; Foletta, Victoria C.; Trieu, Jennifer; Chee, Annabel; Read, Suzannah J.; Naim, Timur; Gregorevic, Paul; et al.
Abstract: Background: Cachexia is a debilitating complication of cancer characterized by progressive wasting and weakness of skeletal muscles that reduces quality of life and can compromise survival. Many anticancer treatments, such as chemotherapy, also cause muscle wasting, which impairs the response to treatment. Given that many cancer patients present with cachexia at the initiation of treatment, we investigated whether cachectic mice were susceptible to chemotherapy‐induced muscle wasting and to investigate contributing mechanisms, including the dysregulation of microRNAs (miRs). Methods: Cachectic colon‐26 (C‐26) tumour‐bearing mice were given 5‐fluourouracil (5‐FU) chemotherapy or vehicle treatment and analysed for muscle mass, fibre size and composition, and miR expression. Mechanisms were validated in vitro using C2C12 cell culture and miR mimics and inhibitors and were confirmed in vivo by injecting muscles of 5‐FU‐treated cachectic mice with recombinant adeno‐associated viral (rAAV) vectors encoding a miR sponge. Results: In cachectic tumour‐bearing mice, 5‐FU chemotherapy exacerbated the loss of skeletal muscle mass compared with vehicle treatment (by −12% to −20%, P  < 0.05). miR expression profiling, quantitative real‐time PCR, and in vitro analyses revealed contributing mechanisms including miR‐351‐3p‐dependent ERK2 inhibition. Intramuscular injection of rAAV vectors encoding a sponge to reduce miR‐351‐3p expression in 5‐FU‐treated cachectic mice enhanced ERK phosphorylation (+18%, P  < 0.05) and increased muscle fibre size (+15%, P  < 0.01). Hsa‐miR‐125a‐3p shares similar predicted gene targets as mmu‐miR‐351‐3p, and its inhibition in human muscle cells in vitro prevented 5‐FU‐induced atrophy ( P  < 0.001) and increased ERK phosphorylation ( P  < 0.001). Conclusions: The findings implicate miR‐351‐3p‐mediated ERK2 inhibition as a contributing mechanism in chemotherapy‐induced muscle wasting in mice with cancer cachexia and that its inhibition is a promising adjunct therapy for preserving muscles during cancer treatment.